Answer:
(x + 3)
Step-by-step explanation:
Using the zero product property
x-a = 0 x-b = 0 where a and b are the zeros
(x-a)(x-b) =0
(x- -3)(x -8) =0
(x+3) (x-8) =0
Combining the like terms, the simplified polynomials are given as follows:
a) 4x² - 14x + 17
b) -5x² - 20x + 8
<h3>How are polynomials simplified?</h3>
Polynomials are simplified combining the like terms, that is, adding these numbers with the same variable.
Item a:
4(x - 2)(x + 1) - 5(2x - 5)
Applying the distributive property:
4(x² - x - 2) - 10x + 25
4x² - 4x - 8 - 10x + 25
Combining the like terms:
4x² - 4x - 10x - 8 + 25
4x² - 14x + 17
Item b:
-5(x + 2)² + 28
-5(x² + 4x + 4) + 28
-5x² - 20x - 20 + 28
-5x² - 20x + 8
More can be learned about the simplification of polynomials at brainly.com/question/24450834
#SPJ1
Answer:
14 deliveries per hour
Step-by-step explanation:
42/3
14
The person makes 14 deliveries per hour
The decimal between it are 6.7
Answer:
x intercept is x=3
y intercept is y=-3
Step-by-step explanation:
We can write this equation in a simpler way to find the values needed. Lets do it. Take:
x-y=3
And sum y in both sides, as we know the equality will maintain:
x-y+y=3+y
x = 3+ y
Now subtract 3 in both sides:
x-3 = y+3-3
x-3=y
So, we can rewrite our equation as y=x-3
The x intercept is a value of x such that the equation in equal to zero; in other words, is the value of x when y is zero. It is also called a zero root. Graphically, its the x value when the function passes trough the x-axis. Lets find if, we nned that:
x-3 = 0
If we sum 3 in both sides:
x-3+3=3
x=3
So, x=3 is x intercept
For finding the y intercept we need the value of y when x is zero. Graphically, is the value of y obtained when the function passes trough the y-axis. So, replace x with 0:
0-3=y
y=-3
Another way to get it is knowing that the y intercept in a polynomial is always the independent term, the one that has no x or y, which in this case is -3.